2018
DOI: 10.1051/matecconf/201817202007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nano-silicon fuel additive on combustion, performance and emission of a twin cylinder CI engine

Abstract: Combustion characteristics of a fuel defines its performance and emission characteristics. Enhancement of combustion characteristics is feasible by improvisation of fuel properties. Fuel additives were used for varying fuel properties. The evolution of ‘nano-concept’ develops countless applications in the existing technologies. In this experiment silicon nanoparticles were synthesized by ball milling micron sized silicon particles for 45 hours. The elemental and structural characterizations for the additive ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The engine torque of D-NA is higher than that of ethanol at 3500 rpm, whereas the engine torque of ethanol is higher at 1000 rpm. Studies by [13], [12], [14], [15], [16], Kader et al (2015), and [17] have identified ethanol as an oxygenate and as a crucial ingredient in enhancing torque at high speeds. Similar to studies by [15] and [16], The ingredients of D-NA, a mix of ethanol and silicon dioxide nanoparticles, influenced the engine's torque.…”
Section: Torquementioning
confidence: 99%
See 4 more Smart Citations
“…The engine torque of D-NA is higher than that of ethanol at 3500 rpm, whereas the engine torque of ethanol is higher at 1000 rpm. Studies by [13], [12], [14], [15], [16], Kader et al (2015), and [17] have identified ethanol as an oxygenate and as a crucial ingredient in enhancing torque at high speeds. Similar to studies by [15] and [16], The ingredients of D-NA, a mix of ethanol and silicon dioxide nanoparticles, influenced the engine's torque.…”
Section: Torquementioning
confidence: 99%
“…Studies by [13], [12], [14], [15], [16], Kader et al (2015), and [17] have identified ethanol as an oxygenate and as a crucial ingredient in enhancing torque at high speeds. Similar to studies by [15] and [16], The ingredients of D-NA, a mix of ethanol and silicon dioxide nanoparticles, influenced the engine's torque. Pure ethanol had the most torque at low speeds, but at 3000 rpm, D-NA surpassed ethanol additive and neat gasoline.…”
Section: Torquementioning
confidence: 99%
See 3 more Smart Citations